Influence of Mn Substitution on Structural and AC magnetic properties of (Ni0.4Cu0.15Zn0.45)1-xMnxFe2O4 with x=0.00, 0.15 - Shara, Afrin Jahan (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Applied Physics and Electronics, 2017.